Pembuatan Klaim Kewargaan (Citizen Claim Making) Pada Masyarakat Nelayan Di Kabupaten Takalar - Miftahul Karima; Andi Yakub; Haryanto Haryanto (Journal of Peace, Security and Democracy, 2026)
This study aims to understand how fishing communities in Aeng Batu-Batu Village, Takalar Regency, construct and negotiate their citizenship claims in their interactions with the state. Using a descriptive qualitative approach within the framework of political sociology, this research explores the social and political practices underlying state–citizen relations in the context of social welfare. Data were collected through in-depth interviews, participatory observations, and document analysis involving 20 informants, including fishermen, village officials, and local figures. The findings reveal three primary forms of citizen claim-making: direct claims to authorities, mediated claims through social intermediaries or political brokers, and collective claims through fishermen’s groups. These forms demonstrate that access to social policies remains highly dependent on patronage networks and personal relationships with local actors. In this context, the state does not function as a neutral institution but rather as a social arena where citizens negotiate their rights through adaptive strategies. Although patron–client relations remain dominant, the study also identifies emerging forms of reflective citizenship, particularly among younger fishermen who use social media to voice injustices. The results affirm that local citizenship practices are dynamic, relational, and continuously shaped through the ongoing process of claim-making that mediates the interaction between citizens and the state.